Considerations on the primary sources that report on the Armada de Molucas’ crossing of the Strait of Magellan Consideraciones acerca de las fuentes primarias que informan sobre la travesía de la Armada de Molucas por el estrecho de Magallanes - Beroš, Mateo Martinić (My University, 2019)
The vicissitudes of Ferdinand Magellan's famous exploration and navigation enterprise enabled the circumnavigation of the globe between 1519 and 1522, were the reason why information about what occurred was initially insufficient though later it proved more satisfactory, although never as much as could be desired at the time and by posterity. The primary sources recount what happened at the time, both in documents originating during the voyage and immediately upon the return of the sole survivor of the five ships comprising the expedition's fleet, along with the circumstances in which such information was obtained or was available. Similarly, the news collected and transmitted later by third parties was always based on reports or news provided by former crew members in a process of accumulation that has taken centuries. Both documentary, written and graphic sources including maps, as well as oral memory are considered as pertaining to the understanding of the formation of the archive collected around this transcendent historical activity.
Keywords: expedition of ferdinand magellan; relations of antonio pigafetta and companions; strait of magellan; third party narratives